DEVELOPMENT OF STUDENT WORKSHEETS REFERRING TO THE ADDIE MODEL - Risa Kumala Sari; Marleni; Jayanti (Esteem Journal of English Education Study Programme, 2024)
The development of Student Worksheets (LKPD) with the help of mentimeter on flat shape material for class V SD Negeri 1 Banyuasin 1, has the aim of being able to produce LKPD on flat shape material with the help of mentimeter which is valid, practical and has potential effects for class V students of SD Negeri 1 Banyuasin1. The type of research used by researchers in developing this LKPD is research and development, development refers to the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were elementary VA class students at SD Negeri 1 Banyuasin 1. Data collection techniques used in the research were interviews, questionnaires, tests and documentation. based on the results of research by validator experts from three fields, namely media, material, language, the developed LKPD media obtained a validity level of 91.51%, from media experts who were categorized as "Very Valid", 90.25% from material experts who were categorized as "Very Valid" , 92.38% of language experts were categorized as "Very Valid" so that the Mentimeter-assisted LKPD was categorized as very valid with revisions. Then the practicality test of the one to one student questionnaire test obtained a result of 92.69% categorized as "very practical", then the small group trial obtained a result of 93.6% categorized as "very practical" so that both obtained a result of 93.1 % "very practical". And the final test of the potential effect test obtained a result of 97.09% categorized as "very effective".